2015
DOI: 10.1017/s0021859614001087
|View full text |Cite
|
Sign up to set email alerts
|

Specific leaf area development of autumn-sown sugar beet (Beta vulgaris L.) on different sowing dates in northern Germany

Abstract: In most regions, sugar beet is normally sown as a spring crop. If sown in autumn the crop remains on the field over winter and may achieve fast re-growth in spring from assimilates stored within the beet, allowing earlier leaf growth and light interception in spring. The specific leaf area (SLA) (ratio between leaf surface and leaf mass) is mainly affected by leaf area expansion and consequently affects productivity in early growth stages. The aim of the present study was (i) to examine the SLA dynamics of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the early growth phase, sugar beet area SLA increased because leaves have less dry matter. Stephan et al [51] and Çakmakçi et al [52] also reported that SLA was higher in the early growth phase.…”
Section: Discussionmentioning
confidence: 94%
“…In the early growth phase, sugar beet area SLA increased because leaves have less dry matter. Stephan et al [51] and Çakmakçi et al [52] also reported that SLA was higher in the early growth phase.…”
Section: Discussionmentioning
confidence: 94%